The Historical Development of Muhammad Arkoun's Thought on the Sacred and the Profane in Islamic Thought - Masdani; Wira Purawata; Ahmad Sirojul Hakiki; Zamroni; Heri Kurniawan (Journal of Indonesian Islamic Studies, 2026)
This study examines Muhammad Arkoun’s thought on the sacred and the profane in Islamic thought and analyzes how these categories shape the historical development of Islamic intellectual traditions. The study is motivated by the persistent epistemological problem in Muslim societies, particularly the tendency to conflate divine revelation with human interpretations, which has contributed to the sacralization of intellectual products, the formation of orthodoxy, and the narrowing of critical inquiry. While previous studies on Arkoun have largely focused on his critique of Islamic reason and hermeneutics, limited attention has been given to the sacred-profane dialectic as a historical structure in Islamic thought. This study employs qualitative library research using historical-intellectual and philosophical approaches. Primary data were obtained from Muhammad Arkoun’s major works, while secondary data consisted of books, journal articles, and other relevant scholarly sources. Data were analyzed using content analysis through thematic, historical, and philosophical interpretation. The findings reveal that Arkoun firmly distinguishes between the sacred, which originates from divine revelation and prophetic experience, and the profane, which consists of human interpretations and socio-historical constructions. The study also shows that the transition from the Qur’anic fact to the Islamic fact marked a crucial transformation in Islamic intellectual history, contributing to the emergence of orthodoxy, sacralization, and epistemological rigidity. Furthermore, social actors such as religious scholars, political authorities, and reformist movements played significant roles in shaping the dynamics of Islamic thought. This study concludes that Arkoun’s Applied Islamology offers an important framework for reconstructing contemporary Islamic thought through a more critical, historical, and contextual approach.